Reciprocity in dynamic employment relationships - Matthias Fahn (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
This paper explores the optimal provision of dynamic incentives for employees with reciprocal preferences. Building on the presumption that a relational contract can establish a norm of reciprocity, I show that generous upfront wages that activate an employee's reciprocal preferences are more important when he is close to retirement. In earlier stages, 'direct' performance-pay promising a bonus in exchange for effort is used more extensively. Then, a longer remaining time horizon increases the employer's commitment which is generally determined by her future profits. Moreover, since future profits are affected by the employee's reciprocal preferences, the norm of reciprocity already shapes the incentive system at the beginning of his career. I also show that more competition might magnify the use of reciprocity-based incentives, and that a formal commitment to paying nondiscretionary wages in the future can boost the employer's credibibility.
Keywords: C73; D21; D86; D90; D91; 330; reciprocity; relational contracts; dynamic incentives